DINAMIKA SISTEM INSTITUSI PENDIDIKAN DI ACEH - Hadi, Abdul (Jurnal Ilmiah Peuradeun, 2014)
Every region has its own educational system that influence by culture and educational system developed by the state (national education system). Both of them are influence students attitude. Hopefully cultural factors in education can form civilized students and national education system form good civil. Apart from that, sometime both of them cannot work together. Aceh?s history proved that this problem still exist in educational system. It can be seen trough the apparance of educational institutions that bring their own main features. This writing attempted to analyze educational system in Aceh that adopted by dayah/pesantren (local terms for traditional Islamic boarding school), Islamic school, and state school.The analyzes are including: educational ideology, educational interaction, student?s arrangements, internalization the spirit of nationalism, and social interaction. The result prove that dayah/pesantren (local terms for traditional Islamic boarding school), Islamic school, and state school, has their own system that different each other. In resume, the differences produce different type of students (attitude).